Web-based application of gold investment plan system (GIPS) / Faridah Aryanti Abdul Rahman - Abdul Rahman, Faridah Aryanti (2015)
Investment is one of business activity to generate income. In Malaysia, there are many types of investment opportunities available for aggressive, moderate and conservative investors. As a result, it can be very tough to decide which investment that is suit for the investors to make money. This research project provides a comprehensive study on gold investment and proposed to develop a software titled Web-based Application of Gold Investment Plan System (GIPS). Beneficial of this project will eliminate the manual process that has been done before, for example using forms and files to keep the investors record. At the same time, it will ease the investors and employees to do an online monitoring of gold investment plan. The study of this project follows qualitative research method, relating to the company‟s requirements as a stakeholder of this research. During development of the system, gold calculation techniques have been used and analysis of the risk had been done. Besides that, system development techniques using Agile methodology was chosen to show clear activities and functions that occur in each phase throughout the project.